Optimization of rice husk hydrochar via microwave-assisted hydrothermal carbonization: Fuel properties and combustion kinetics - Zulkornain M.F. (Elsevier Ltd, 2023)
Biofuels; Calorific value; Carbonization; Combustion; Combustion kinetics; Fuel properties; Higher heating value; Hydrothermal carbonization; Microwave-assisted hydrothermal; Microwave-assisted hydrothermal carbonization; Optimisations; Rice husk; Solid bio-fuels; Solid yield; Thermochemistry; biofuel; carbon; fuel; lignite; volatile agent; Article; ash; carbonization; combustion; controlled study; decarboxylation; decomposition; deoxygenation; elemental analysis; experimental design; heating; kinetics; microwave radiation; moisture; reaction optimization; reaction time; response surface method; retention time; rice husk; temperature; thermogravimetry; validation process